2001
DOI: 10.1088/0953-4075/34/14/303
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical signature in spatial spin distributions of relativistic electrons

Abstract: The time-dependent Dirac equation has been solved for an electron in external static electric, static magnetic and time-dependent electromagnetic fields. We give several examples of how the dynamics of the spin variables can couple to the relativistic orbital motion and investigate the time evolution of the spatial spin distribution as a function of the position for a relativistic quantum state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Both studies found negligibly small spin effects. We note that the influence of the electron spin has also been investigated with respect to free-electron motion [14], bound-electron dynamics [15], atomic photoionization [16], and Compton and Mott [17] scattering in strong plane-wave laser fields.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies found negligibly small spin effects. We note that the influence of the electron spin has also been investigated with respect to free-electron motion [14], bound-electron dynamics [15], atomic photoionization [16], and Compton and Mott [17] scattering in strong plane-wave laser fields.…”
Section: Introductionmentioning
confidence: 99%
“…At early times, the packet is non-relativistic and we see the concentric ring-like contour lines reminiscent of those of the non-relativistic orbits. [28] The region around the origin has the smallest velocity contributions and therefore the smallest amount of Lorentz contraction. It is quite remarkable that even at later times (t> 0.4 a.u.…”
Section: Spin-densities Of Cycloatomsmentioning
confidence: 99%
“…Most of the previous theoretical studies were done in non-relativistic framework. In the field of relativistic quantum mechanics most of the efforts have been focused on the problem of the interaction between the atoms and a mixture of static fields with, most of the time, intense laser fields [2][3][4][5][6][7][8][9][10][11]. Under these conditions the use of a relativistic theory is fully justified since the external field is then able to bring considerable energy to the WP.…”
mentioning
confidence: 99%
“…For n = 50, ǫ = 0.4 precession time T p ranges from 1.96 • 10 −11 s for Z = 92 to 1.4 • 10 −3 s for Z = 1. T K in (10) denotes the Kepler period.…”
mentioning
confidence: 99%
See 1 more Smart Citation